Identifikasi Fasade Bangunan Peninggalan pada Rumah Tinggal di Kecamatan Banda Sakti Kota Lhokseumawe - Armelia Dafrina; Fidyati Fidyati; Riza Fitri; Nova Purnama Lisa (Fakultas Teknik, 2020)
Colonial architecture is an architectural style from a mixture of European architecture and through a process of adaptation to form Dutch architecture during the Indonesian era during the Dutch colonialism. This colonial architecture adapted to the local environment and climate in order to produce buildings that were suitable and comfortable to live in. The research object is the residential house in Banda Sakti District, Lhokseumawe City. This area is a place where there are historical buildings identified as the Dutch Colonial Heritage Area. The aim of this research is to identify the existence of houses in Banda Sakti District, Lhokseumawe City through the building facades which still have the characteristics of Dutch colonial architecture. This research method is a qualitative research method through direct observation at the research location and interviews of home owners. The research focuses on the elements of the outdoor facade that are related to the exterior of the building. The identification resulted that eight residential houses in Banda Sakti District still used the architectural features of the colonial building façade, but 2 of them had adapted to the times.